Analisis manajemen risiko layanan mobile banking pada bank syariah - Hidayah, Nurul (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the risks of using mobile banking services I sharia financial institutions. With the existence of mobile banking services, it makes it easier for customer or users to carry out transactions at any time and anywhere. The benefits of mobile banking also have risks such as fraud, account numbers being hacked and many more. So to anticipate this, banking institutions must think more about how to overcome these risks so that customers remain satisfied using mobile banking services.